PENGGUNAAN METODE MIND MAPPING PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI KELAS XII MADRASAH ALIYAH UNGGULAN DARUL FALAH MOJOKERTO - Maisyaroh, Evi Lailatul; Hosna, Rofiatul (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
The use of the mind mapping method was able to improve the quality of learning in the subject of Islamic Cultural History at Madrasah Aliyah Darul Falah Class XII (Twelve) Mojokerto Regency. This Mind Mapping nethod can improve the quality of learning, especially in the subject of Islamic Cultural History. The Mind Mapping method is a way of making notes that are not boring with words, colors, lines, and pictures. To achieve the expected learning objectives, educators need to use learning models that can increase the activity and effectiveness of teaching and learning activities. The learning model in question is the Mind Mapping learning model, which is a creative, effective way of taking notes and mapping our thoughts in an interesting and easy way and not boring.